2018
DOI: 10.1074/mcp.ra118.000670
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Phloem Sap mRNA and Protein Expression Analysis Reveals Phytoplasma-infection Responses in Mulberry

Abstract: To gain insight into the response of mulberry to phytoplasma-infection, the expression profiles of mRNAs and proteins in mulberry phloem sap were examined. A total of 955 unigenes and 136 proteins were found to be differentially expressed between the healthy and infected phloem sap. These differentially expressed mRNAs and proteins are involved in signaling, hormone metabolism, stress responses, etc. Interestingly, we found that both the mRNA and protein levels of the major latex protein-like 329 () gene were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…Our data also showed that MuPR1-GFP fusion was localized exclusively to the extracellular spaces (Figure 4(c)). This is consistent in that some PR1s were detected in the phloem saps of several plants, including mulberry, cucurbits, rice, and Arabidopsis (Walz et al 2004;Deeken et al 2008;Gutierrez-Carbonell et al 2015;Gai et al 2018), and some PR1s exhibit vascularspecific expression patterns (Carr et al 1987;Tornero et al 1997). Therefore, MuPR1 proteins could be secreted into the phloem and may play an important role in SAR.…”
Section: Discussionsupporting
confidence: 78%
“…Our data also showed that MuPR1-GFP fusion was localized exclusively to the extracellular spaces (Figure 4(c)). This is consistent in that some PR1s were detected in the phloem saps of several plants, including mulberry, cucurbits, rice, and Arabidopsis (Walz et al 2004;Deeken et al 2008;Gutierrez-Carbonell et al 2015;Gai et al 2018), and some PR1s exhibit vascularspecific expression patterns (Carr et al 1987;Tornero et al 1997). Therefore, MuPR1 proteins could be secreted into the phloem and may play an important role in SAR.…”
Section: Discussionsupporting
confidence: 78%
“…P. aurantifolia’ (Monavarfeshani et al, 2013). Increased expression of the gene that encodes the PR-1 protein was shown for mulberry phloem sap infected with phytoplasmas (Gai et al, 2018a).…”
Section: Salicylic Acidmentioning
confidence: 99%
“…Ectopic expression of this gene enhances mulberry resistance to several pathogens, including phytoplasmas. Although treatment of wild-type mulberry seedlings with SA did not affect MuMLPL329 expression, the PR-2 and PR-5 genes were highly expressed in MuMLPL329 -overexpressing transgenic Arabidopsis plants (Gai et al, 2018a).…”
Section: Salicylic Acidmentioning
confidence: 99%
See 2 more Smart Citations